Gas Preconcentrator Made by Rolling up a Printed Hotplate on Foil. (2015) - Camara, M.; Rieu, M.; Breuil, P.; Pijolat, C.; Briand, D.; de Rooij, N.F.
Abstract: This paper presents the design and implementation of a foil gas preconcentrator (FGP) on polyimide (PI) substrate. One novelty of the paper is that our device is made on flexible foil by using printing whereas all preconcentrators seen in literature are mainly based on rigid substrates and are micro-machined using cleanroom processes. Printing allows the additive and localized deposition of materials at low temperature on large area and can be applied to both the patterning of the heating element and the integration of the gas absorbent material. The benefits are the easy and flexible processing of cost-effective and lightweight preconcentrators for a variety of target gases. The tubular shape of the FGP is obtained by rolling up and sealing the inkjet printed gold hotplate on foil, which is then filled with the gas absorbent material (Carbopack B and Tenax). The diameter of the inlet/outlet of FGP is adjustable leading to high flow rates, up to 1.5 L/min, much larger than their silicon counterpart. The concept was validated using two target gases (Benzene and Acetophenone) at concentrations down to 250 ppb.